Performances of a wind power system based on the doubly fed induction generator controlled by a multi-level inverter - Mohamed Salah Djebbar; Aziz Boukadoum; Abla Bouguerne (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
The objective of this work is to study the contribution that the use of the multi-level inverter can make compared to a conventional two-level inverter, in a wind power production line (WPG) associated with a doubly fed induction generator (DFIG). The DFIG is driven by a variable speed wind turbine and operates in maximum power point tracking (MPPT) mode, for optimum efficiency. The rotor of the DFIG is supplied by a DC/AC inverter with five levels with MPC structure, controlled by the PWM technique, while the stator is connected with the network. The active and reactive powers exchanged between the DFIG and the network is achieved by indirect vector control with oriented stator flux (IFOC), with conventional regulators, ensuring zero reactive power and a unitary power factor. The total harmonic distortion (THD) of the current signals/voltages of the entire wind chain is exposed and criticized. The obtained results are very promising, offering the possibility for wind turbines with multi-level inverter to work in high voltage and large power.